Design and Investigation of 10 Gb/s FSO Wiretap Channel Using OCDMA Time-Diversity Reception - Jianhua Ji; Bing Wu; Jianjia Zhang; Ming Xu; Ke Wang (IEEE Photonics Journal)
In this paper, 10 Gb/s free space optical (FSO) wiretap channel using optical code division multiple access (OCDMA) time-diversity reception is designed and demonstrated for the first time. Reliability and security are investigated under weak and strong turbulence conditions. Two-dimensional optical encoder and decoder are constructed by wavelength selective switches and optical delay lines, and one-dimensional optical encoder and decoder are constructed by couplers and tunable optical delay lines. Experimental results show that reliability and security can be enhanced simultaneously using OCDMA time-diversity reception. At the received power of 2.58 dBm in strong turbulence, compared to non-diversity system, bit error rate (BER) of legitimate user in OCDMA time-diversity system is reduced from 3.9 × 10−7 to 6.73 × 10−8. Furthermore, the reliability improvement is more obvious when the correlation between the two signals of OCDMA time-diversity is smaller. The secrecy capacity can be increased from 0.546 bit/symbol to 0.665 bit/symbol in strong turbulence when received power is 2.28 dBm. On the other hand, the secrecy capacity of strong turbulence is about 15% higher than that of weak turbulence.